2014
DOI: 10.1007/s00590-013-1409-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating spinal cord distraction injuries: the effect of durotomy in decreasing cord interstitial pressure in vitro

Abstract: Spinal cord distraction causes elevations in CIP. Durotomy lowers elevated CIP in vitro and may be effective at lowering CIP in vivo. Further study is required to evaluate the usefulness of durotomy in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“… 23 Durotomy also reduced interstitial spinal cord pressure after TSCI in ex vivo pig spinal cords. 24 In rodent models of TSCI, durotomy with duroplasty improves outcome more than durotomy without duroplasty. 25 In rats, durotomy without duroplasty is associated with more macrophage accumulation, cystic cavitation and fibroblast proliferation than durotomy with duroplasty.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Durotomy also reduced interstitial spinal cord pressure after TSCI in ex vivo pig spinal cords. 24 In rodent models of TSCI, durotomy with duroplasty improves outcome more than durotomy without duroplasty. 25 In rats, durotomy without duroplasty is associated with more macrophage accumulation, cystic cavitation and fibroblast proliferation than durotomy with duroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…In a pig contusion TSCI model, increased thecal sac dimensions were associated with reduced cord compression and reduced injury site ISP [ 28 ]. Durotomy reduced intraparenchymal ISP after TSCI in ex-vivo pig spinal cords [ 29 ]. In a rat contusion TSCI model, durotomy with duroplasty improved outcome more than durotomy without duroplasty [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have examined durotomy use for the treatment of SCI. The possible mechanisms of the neuroprotective effect of a durotomy are as follows: a decrease in CIP [ 8 ], cavitation, scar formation, and lesional volume [ 9 ]; relief of congestive epidural veins; and restoration of CSF flow [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggested that decompression only by removal of osseous and soft-tissue elements might not be adequate and should be further improved to restore normal CIP. Waleed et al found a durotomy could lead to a dramatic CIP drop in a distraction SCI model in vitro [ 8 ].…”
Section: Introductionmentioning
confidence: 99%